Encyclopedia of Embroidery Stitches, Including Crewel - Marion Nichols (USA Dover Publications, 1974)
An encyclopedic handbook on embroidery that provides precise explanations and clear illustrations on how to work 178 different stitches and their variations.
Includes index.
Keywords: Applied Sciences (3GdYdhe GdJWHjbjIs; Embroidery; General